The α7 nicotinic acetylcholine receptor agonist, GTS-21, attenuates hyperoxia-induced acute inflammatory lung injury by alleviating the accumulation of HMGB1 in the airways and the circulation - Ravikumar A. Sitapara; Alex G. Gauthier; Sergio I. Valdés-Ferrer; Mosi Lin; Vivek Patel; Mao Wang; Ashley T. Martino; Jeanette C. Perron; Charles R. Ashby; Kevin J. Tracey; Valentin A. Pavlov; Lin L. Mantell (BMC, 2020)
Abstract Background Oxygen therapy, using supraphysiological concentrations of oxygen (hyperoxia), is routinely administered to patients who require respiratory support including mechanical ventilation (MV). However, prolonged exposure to hyperoxia results in acute lung injury (ALI) and accumulation of high mobility group box 1 (HMGB1) in the airways. We previously showed that airway HMGB1 mediates hyperoxia-induced lung injury in a mouse model of ALI. Cholinergic signaling through the α7 nicotinic acetylcholine receptor (α7nAChR) attenuates several inflammatory conditions. The aim of this study was to determine whether 3-(2,4 dimethoxy-benzylidene)-anabaseine dihydrochloride, GTS-21, an α7nAChR partial agonist, inhibits hyperoxia-induced HMGB1 accumulation in the airways and circulation, and consequently attenuates inflammatory lung injury. Methods Mice were exposed to hyperoxia (≥99% O2) for 3 days and treated concurrently with GTS-21 (0.04, 0.4 and 4 mg/kg, i.p.) or the control vehicle, saline. Results The systemic administration of GTS-21 (4 mg/kg) significantly decreased levels of HMGB1 in the airways and the serum. Moreover, GTS-21 (4 mg/kg) significantly reduced hyperoxia-induced acute inflammatory lung injury, as indicated by the decreased total protein content in the airways, reduced infiltration of inflammatory monocytes/macrophages and neutrophils into the lung tissue and airways, and improved lung injury histopathology. Conclusions Our results indicate that GTS-21 can attenuate hyperoxia-induced ALI by inhibiting extracellular HMGB1-mediated inflammatory responses. This suggests that the α7nAChR represents a potential pharmacological target for the treatment regimen of oxidative inflammatory lung injury in patients receiving oxygen therapy.